HEART BLOCK AS A COMPLICATION OF ACUTE MYOCARDIAL INFARCTION, CLINICAL ASSESSMENT AND APPROACH. A CASE REPORT - Jashari, Enes; Murtezani, Besir; Zhaku, Vegim (Faculty of Medical Sciences, University of Tetova, 2023)
Optimal treatment for acute ST-elevation myocardial infarction (STEMI) within 12 hours after symptom onset includes primary percutaneous coronary intervention (PCI) or thrombolytic therapy. For STEMI patients who present later than 12 hours, current guidelines do not recommend PCI except the presence of hemodynamic or electrical instability or continuing ischemic symptoms. Thus, our intention is to show that early reperfusion may also play a role in the early recovery of AV block that may occur as a complication of myocardial infarction (MI), more commonly inferior MI. Patient 49 years old patient (male) presented in our department with weakness, dizziness, short-term instability and nausea. The symptoms started one day before admission. The ECG on admission showed a total AV block with a heart rate approximately 33 b/min and ST segment elevation in the inferior leads. Laboratory tests were normal except for an extreme elevated high sensitive troponin. The echo showed normal finding with the exception of the slightly reduced kinetics of the apex, base and mid segment of the lower-posterior wall of the IVS. Coronary angiography was immediately performed, showing 100% stenosis of the rPDA. A stent is placed on the corresponding coronary artery. The total block was present all the time, and following the recommendations, a temporary pacemaker was placed in the patient due to hemodynamic instability and bradycardia. Despite reperfusion, the block persisted 7 days after the intervention, during which a permanent pacemaker was implanted and the patient was discharged for home treatment. This case highlights the importance and ways of early reperfusion to improve outcomes in patients with STEMI. Early reperfusion may also play a role in the early recovery of AV block that may occur as a complication of MI, more commonly inferior MI.
Keywords: heart block; myocardial infarction; percutaneous coronary intervention